Protocol to assess substrate dephosphorylation by serine/threonine phosphoprotein phosphatases in vitro - Jason S. Wasserman; Felicity Feiser; Seren Palacio; Kishan Patel; Joy Gonzalez; Holly Fowle; Xavier Graña (STAR Protocols, 2023)
Summary: Serine/threonine protein phosphatase 2 (PP2A) forms heterotrimeric holoenzymes, where a scaffold subunit bridges the PP2A catalytic subunit to a B regulatory subunit, e.g., B55α. The PP2A/B55α holoenzyme plays key roles in signaling and cell-cycle control targeting multiple substrates. Here, we describe semiquantitative approaches to determine PP2A/B55α substrate specificity. Parts I and II detail approaches to assess PP2A/B55α-mediated dephosphorylation of immobilized substrate peptide variants. Parts III and IV detail methods to assess PP2A/B55α-substrate-binding specificity. These approaches are adaptable to other serine/threonine phosphatases.For complete details on the use and execution of this protocol, please refer to Fowle et al..1 : Publisher’s note: Undertaking any experimental protocol requires adherence to local institutional guidelines for laboratory safety and ethics.